MEDICINAL, COSMETIC, CHEMICALAND OTHER APPLICATIONS OF BORATES - Sadia Hafeez Kazi et al (Baqai Journal of Health Sciences)
Boron and its related compounds are found in abundance in nature such as soil, water, and plants. Use of borates dates back to the time of Babylonians and Egyptians, some 4000 years ago, for gold refining and mummifying the dead. It was later discovered as a useful laboratory and industrial agent along with an effective antiseptic and insecticidal compound. In combination with other compounds, boron complexes showed a positive effect as an anticancer agent. Currently, borates are extensively employed in the field of medicine, dentistry, cosmetology, nuclear, aeronautical fuels, weaponry, agricultural, chemicals, etc. Moreover, they are also used in industrial processes as abrasives, refractories, flame retardants, glazes, frits, enamels, and metallurgy. The various characteristics of borates including its application are discussed and reviewed in this article, which may be beneficial for researchers in the development of various scientific and technological fields.